CASE STUDY OF FINANCIAL STRATEGY IN THE DEVELOPMENT & OBSTACLES OF STREET VENDORS IN SURABAYA - Suryawijaya, Alan; Dewi, Liliana (Universitas Ciputra Surabaya, 2018)
This study aims to find out what factors are hampering the BEST APKLI (Asosisasi Pedagang Kaki Lima Indonesia/Indonesian Food and Drink Street Vendors Association) partnership concept for street food vendors category A in Gubeng Regency Surabaya, Indonesia, The study is classified as a case study. The street vendors were selected based on purposive sampling with related selection based on the accessibility between researchers and the source. The study found that business capital is not an inhibiting factor in the development of MSMEs (micro, small, and medium enterprise).